Data protection in Malaysia: the year in review - Zulhuda, Sonny (2019)
This presentation is on the review of the data protection law and challenges in Malaysia in the year 2019. This is an update on how the law has been implemented in Malaysia, including the recent issues that emerge. It ends up sharing on the prominent issues that become the focus for law review/amendment proposals,